Endometriose: Recomendações de consenso nacionais - clínica e diagnóstico - Aguiar,Ana (2016)
Overview and aims: This article summarises the Portuguese endometriosis consensus elaborated in order to adapt to our population the consensus documents published in the literature. Endorsed by the Portuguese Society of Gynaecology, we established recommendations that provide guidance to our medical society to better decision making concerning the assistance of patients with endometriosis, to improve diagnosis and to optimize management. We expose here a short version of the first section of the guidelines, addressing the clinical and diagnosis management of this disease. Study design and Methods: The European Society of Human Reproduction and Embryology (ESHRE) guideline for the diagnosis and treatment of endometriosis (2014) was the reference paper for these clinical recommendations in endometriosis. A group of experts in the field performed a thorough systematic search of the publications between January 2012 up to December 2014 and a quality assessment of the included papers. A consensus meeting with all members of the guidelines developing group reached the final version of the recommendations. Conclusions: The present clinical practice guidelines on endometriosis may improve the accurate clinical and imaging diagnosis of pelvic and extra pelvic endometriosis and enhance endometriosis risk assessment and care.